Effects of Curcumin on Parameters of Myocardial Oxidative Stress and of Mitochondrial Glutathione Turnover in Reoxygenation after 60 Minutes of Hypoxia in Isolated Perfused Working Guinea Pig Hearts - Ermita I. Ibrahim Ilyas; Busjra M. Nur; Sonny P. Laksono; Anton Bahtiar; Ari Estuningtyas; Caecilia Vitasyana; Dede Kusmana; Frans D. Suyatna; Muhammad Kamil Tadjudin; Hans-Joachim Freisleben (Hindawi Limited, 2016)
In cardiovascular surgery ischemia-reperfusion injury is a challenging problem, which needs medical intervention. We investigated the effects of curcumin on cardiac, myocardial, and mitochondrial parameters in perfused isolated working Guinea pig hearts. After preliminary experiments to establish the model, normoxia was set at 30 minutes, hypoxia was set at 60, and subsequent reoxygenation was set at 30 minutes. Curcumin was applied in the perfusion buffer at 0.25 and 0.5 μM concentrations. Cardiac parameters measured were afterload, coronary and aortic flows, and systolic and diastolic pressure. In the myocardium histopathology and AST in the perfusate indicated cell damage after hypoxia and malondialdehyde (MDA) levels increased to 232.5% of controls during reoxygenation. Curcumin protected partially against reoxygenation injury without statistically significant differences between the two dosages. Mitochondrial MDA was also increased in reoxygenation (165% of controls), whereas glutathione was diminished (35.2%) as well as glutathione reductase (29.3%), which was significantly increased again to 62.0% by 0.05 μM curcumin. Glutathione peroxidase (GPx) was strongly increased in hypoxia and even more in reoxygenation (255% of controls). Curcumin partly counteracted this increase and attenuated GPx activity independently in hypoxia and in reoxygenation, 0.25 μM concentration to 150% and 0.5 μM concentration to 200% of normoxic activity.